ARCHAIC WORD USAGE IN ENGLISH LITERARY WORKS - Martina Girsang; Dian Elizabeth Octavia Nababan; Kevin Gideon Barus; Meylin Mutiara Panjaitan; Sri Melawati Hutasoit (Media Bina Ilmiah, 2023)
Prose as a form of literary work is a form of writing both fiction and nonfiction with certain elements and characteristics. The study aims to assess the use of archaic words in English prose literary works. Archaic words refer to ancient words whose use is no longer common today. The research uses a descriptive method that comprehensively reviews the use of archaic words in English prose literary works. Generally, the use of archaic words in English prose literary works can be found in medieval English literary works. The use of archaic words in English literary works is still preserved until today with the aim of providing color and sharpening the meaning of the words of a prose to the reader.